If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -7y = 2y + 8 Combine like terms: 5y + -7y = -2y -2y = 2y + 8 Reorder the terms: -2y = 8 + 2y Solving -2y = 8 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -2y + -2y = 8 + 2y + -2y Combine like terms: -2y + -2y = -4y -4y = 8 + 2y + -2y Combine like terms: 2y + -2y = 0 -4y = 8 + 0 -4y = 8 Divide each side by '-4'. y = -2 Simplifying y = -2
| x=175000+.1x | | x^2+10n-39=0 | | 20=2g+3g | | (6x-1)(4x+6)= | | -3x-1y=-13 | | e^4=16 | | e^4=6 | | Los(x+25)=3 | | 21x+115=-3x^3+12x^2+17 | | (2x-5)=-3 | | 9/16-33/4 | | 16r+15=-r^2 | | 9y-30=60 | | 3k^2-27k+10=0 | | 5n+119=14n-7 | | 12*x+48=51*x-117 | | X=16a+1 | | 77077= | | 2y=y+11 | | (2x-4)/x=2 | | Ln(x^2-1)=1 | | X+.09x=11 | | 3(2-3x)-4=-(4x-5)+2 | | 62x+110=668 | | 62x+110=168 | | 5/6/1/7 | | Y-3=0(x-4) | | 2x+3=4(2+1) | | content://media/external/file/31459 | | 3x+7=12x+6 | | 9x-11=x+10 | | 16+9x-1-5x=-15+10x |